2011
DOI: 10.1016/j.pmrj.2010.12.024
|View full text |Cite
|
Sign up to set email alerts
|

The Female Athlete Triad and Endothelial Dysfunction

Abstract: A tremendous increase in the number of female athletes of all ages and abilities has occurred in the past 35 years. In general, sports and athletic competition produce healthier and happier women. However, explosion in participation has revealed clear gender-specific injuries and medical conditions unique to the female athlete. This article focuses on the latest advances in our knowledge of the female athlete triad and the relationship between athletic-associated amenorrhea and endothelial dysfunction. Treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 64 publications
(75 reference statements)
0
16
0
1
Order By: Relevance
“…A patient with hypoestrogenemia and amenorrhea may have the same steroid hor- 33,34 Further, low energy availability has been linked to negative cardiovascular effects such as decreased vessel dilation leading to decreased tissue perfusion and hastened development of atherosclerosis. 33 Female athletes with hypoestrogenism may show reduced perfusion of working muscle, impaired aerobic metabolism in skeletal muscle, elevated low-density lipoprotein cholesterol, and vaginal dryness.…”
Section: Diagnosing Menstrual Dysfunctionmentioning
confidence: 99%
“…A patient with hypoestrogenemia and amenorrhea may have the same steroid hor- 33,34 Further, low energy availability has been linked to negative cardiovascular effects such as decreased vessel dilation leading to decreased tissue perfusion and hastened development of atherosclerosis. 33 Female athletes with hypoestrogenism may show reduced perfusion of working muscle, impaired aerobic metabolism in skeletal muscle, elevated low-density lipoprotein cholesterol, and vaginal dryness.…”
Section: Diagnosing Menstrual Dysfunctionmentioning
confidence: 99%
“…(1985), larger board size can affect corporate performance. Lanser (1969) Yermack (1996) found that a large board size has a small, insignificant and negative effect on performance. Guest (2009) suggests that a company could be more effective with a small board size because it would reduce the problem of poor communication and piggybacking on the boards.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As indicated in Chapter 5, if iron status tests are indicative of iron deficiency, then iron supplementation under the supervision of the athlete's physician and a registered dietitian is warranted. Finally, there is some research to suggest that folic acid supplementation may be beneficial for treating the endothelial dysfunction that often accompanies low EA and menstrual dysfunction in female athletes (Hoch et al 2010(Hoch et al , 2011aLanser et al 2011). To date, three studies have demonstrated significant improvements in FMD with folic acid supplementation (10 mg/day for 4 weeks) Downloaded by [University of Idaho Library] at 12:10 14 June 2016 in female athletes (runners and ballet dancers) (Hoch et al 2010(Hoch et al , 2011aLanser et al 2011).…”
Section: Strategies To Correct Low Energy Availability Among Female Amentioning
confidence: 99%